Avaliação de cenários para a gestão dos resíduos domiciliares na região norte do Vale do Paraíba/SP - Deus, Rafael Mattos de [UNESP] (2015)
Solid waste is a challenge for public administration because it increases as population grows. Thus, Brazil's National Policy on Solid Waste traced goals to solve of the problems (e.g., replacement of open dumps with controlled ladfills); however, effectively achieving the goal is not simple. There are viable alternatives such as inter-municipal cooperation by consortium and privatization. Furthermore, integrated management involves various tecniques, strategies, and programs to achieve certain goals. As a result, we aimed to evaluate greenhouse gas (GHG) emissions and energy consumption in six regional landifill scenarios: conventional, with 10% less waste generation, with 10% additional waste generation, with 20% recycling, with 20% composting. Each was considered in two contexts (inter-municipal cooperation and privatized) for small municipalities located in the north of Vale do Paraíba/SP. Through scenario-building and use of the waste reduction model, total energy in BTU, emissions in metric tons carbon equivalent (MTCE) were evaluated in various situations. When waste increases, so do GHG emissions and energy consumption; therefore a municipal program to reduce waste generation contributes favorably. The best scenario is one that integrates composting and recycling, contributing to a 72% reduction in MTCO2E and MTCE emissions, and differing 410% in energy use, avoiding it consumption. The consortium context will be effective only if the location is ideal because transportation is an important part of the environmental impact